Rheological and Physical Properties of Mucilage Hydrogels from Cladodes of Opuntia ficus-indica: Comparative Study with Pectin - Federica Torregrossa; Matteo Pollon; Giorgia Liguori; Francesco Gargano; Donatella Albanese; Francesca Malvano; Luciano Cinquanta (Gels, 2025)
The physical and rheological properties of mucilage hydrogels derived from the cladodes of Opuntia ficus-indica (L. Mill) were compared with those of commercial pectin for potential applications in the food industry. All hydrogels—formulated by incorporating sucrose and either calcium chloride or calcium carbonate to promote favorable gel network formation—exhibited pseudoplastic (shear-thinning) behavior. The flow characteristics of the hydrogels prepared with mucilage or pectin conformed to the Casson fluid model. Moreover, all samples consistently displayed loss modulus (G″) values exceeding their corresponding storage modulus (G′) values, indicating a dominant viscous behavior over elastic properties. The ζ-potential of all samples was negative across the pH range studied. Mucilage-based samples exhibited lower ionizability per unit mass and reduced phase stability compared to those containing pectin. Principal component analysis (PCA) revealed that mucilage hydrogels exhibited multivariate profiles similar to pectin hydrogels containing calcium carbonate, though the latter demonstrated greater polydispersity than standard pectic gels. Infrared spectroscopy further highlighted distinct spectral differences between pectins and mucilages, offering valuable insights into their respective functional characteristics. Collectively, these findings underscore the potential of Opuntia ficus-indica mucilages as viable additives in food formulations.